Crack growth at fastener holes containing intergranular cracking. (March 2015) - Peng, D.; Jones, R.; Lo, M.; Bowler, A.; Brick, G.; Janardhana, M.; Edwards, D.
Highlights: Previous studies of crack growth at holes with intergranular cracking were limited to idealised intergranular cracks. This paper is the first to study load transfer across the intergranular cracks. This study suggests that intergranular cracks at holes have only a small effect on life. Abstract: This paper describes the results of a continuing study into a new class of multi-site damage problems, viz: the interaction between intergranular cracks and cracks that grow from small naturally occurring material discontinuities at a fastener hole, and extends the findings of the prior investigation by considering the effect of contact between opposing faces of the intergranular cracks. This study suggests that, for the particular problem analysed, the level of contact between the opposing surfaces of the intergranular cracks has little effect on crack growth and that intergranular cracks have little effect, i.e. less than approximately 11%, on crack growth.